Public participation in health: theory, policy and practice in user involvement in cancer-genetics pilots - Martin, Graham Paul (2009)
Public participation is an increasingly prominent policy in the United Kingdom and elsewhere. This thesis locates one example of participation within wider debates about the constitution of contemporary society, changing welfare-state governance, and the challenges of operationalizing such initiatives. It relates the particularities of this case to practical, policy and theoretical questions.